2021
DOI: 10.4136/ambi-agua.2582
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogel in the seedling growth of Eucalyptus dunnii Maiden under different irrigation management

Abstract: This study evaluated the effect of using hydrogel in the planting of Eucalyptus dunnii seedlings in pots, under different water-management regimens. Seedlings of approximately 25 cm height were planted in pots filled with 4.5 L of soil. The experiment was of Completely Randomized Design, in a 2x3 factorial, with absence and presence of hydrogel related to different water-management regimens (irrigation only in planting, every 3 to 6 days). From planting until the 47th day the seedlings were evaluated for the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
1
0
0
1
Order By: Relevance
“…The linear increase observed in the Chl b index ( Figure 4 d) may be due to a negative adjustment of the enzymatic activity of Chl b reductase, responsible for the conversion of Chl b to Chl a [ 33 ], indicating that the photosynthetic apparatus is suffering damage in the chlorophyll fluorescence, which can be confirmed by observing the fluorescence data ( Figure 5 ), which showed damage in the PSII. Behavior similar to our study was observed by [ 34 ] in eucalyptus ( Eucalyptus dunnii Maiden ) on the ground with a water-retaining polymer, which found increases in leaf chlorophyll levels depending on the irrigation frequency. The authors attributed to the water-retaining polymer a reduction in nutrient losses, mainly N, which is directly linked to the structuring composition of photosynthetic pigments in plants.…”
Section: Discussionsupporting
confidence: 91%
“…The linear increase observed in the Chl b index ( Figure 4 d) may be due to a negative adjustment of the enzymatic activity of Chl b reductase, responsible for the conversion of Chl b to Chl a [ 33 ], indicating that the photosynthetic apparatus is suffering damage in the chlorophyll fluorescence, which can be confirmed by observing the fluorescence data ( Figure 5 ), which showed damage in the PSII. Behavior similar to our study was observed by [ 34 ] in eucalyptus ( Eucalyptus dunnii Maiden ) on the ground with a water-retaining polymer, which found increases in leaf chlorophyll levels depending on the irrigation frequency. The authors attributed to the water-retaining polymer a reduction in nutrient losses, mainly N, which is directly linked to the structuring composition of photosynthetic pigments in plants.…”
Section: Discussionsupporting
confidence: 91%
“…Além da técnica de mulching, o uso de hidrogel minimiza o déficit hídrico, pois possui capacidade de retenção de água, pois libera gradualmente a água retida para o solo após a hidratação, disponibilizando-a para absorção pelas raízes das plantas (NAVROSKI et al, 2014). Sua utilização influencia no desenvolvimento das raízes, crescimento e desenvolvimento das plantas, maximiza o aproveitamento da água (de irrigação ou precipitação), melhora a aeração e drenagem do solo, diminui o déficit hídrico em períodos de estiagem, além de reduzir as perdas de nutrientes por lixiviação, diminuindo os custos na produção de diferentes culturas e possibilitando maior flexibilidade entre operações de irrigação (SAAD et al, 2009;NAVROSKI et al, 2014;FELIPPE et al, 2021).…”
Section: Introductionunclassified